Maternal Vitamin D Levels in Gestation - An Observational Cross Sectional Study in the Rural Population of South India - Amalraj, Julie Christy; ., Andal; Saraswathi, Perumal; Dorairaj, Swayam Jothi; Sumathy, Dr. G. (International Journal of Innovative Research in Medical Science, 2019)
Background:Vitamin D* called the sunshine vitamin is essential throughout life. Pregnancy is an altered physiological state in women, which requires proper nourishment. During gestation, this vitamin also plays an important role in development of the fetus. Objective:To observe the serum vitamin D (25diohydroxycholicalciferol) levels and serum calcium levels in the maternal blood during the three trimesters. Design: Observational Cross sectional study. Study population: Rural Mothers from Kancheepuram District, Tamil Nadu South India. We used 50 antenatal blood samples as experimental group and 15 as control group. The age group included 20-40 years. Blood samples were collected from 50 antenatal mothers between 20 – 40 years age group, from Obstetrics and Gynecology OPD for their routine antenatal check-ups, after getting duly signed informed consent. Control group had 15 women in the same age group not pregnant. Results: The results were tabulated. The mean value of 25dihydroxy vitamin D was observed very low than normal levels in all the three trimesters. The mean value of serum vitamin D in first trimester was 50.87 ng/ml, mean value of serum vitamin D in second trimester was 54.05.ng/ml, and mean third trimester vitamin D was 61.24ng/ml which was well below the optimum level of 100ng/ml. Conclusion: The vitamin D deficiency with normal level maintenance of serum calcium shows the compensatory mechanism that involves the normal calcium level maintence with resorption of bones by the osteoclastic actions to correct the deficit. If the deficiency is left untreated it may lead to faster osteoporosis in the mother. *25 dihydroxycholicalciferol